Colonial Structure And Andean Insurgency - Bonilla, Heraclio (Universidad del Pacífico, 1977)
From the same moment the Spanish conquest of the Andean area, indigenous people played a leading role in various social movements that were expressed on the one hand, opposition to imperial domination, on the other hand, the abuses of the colonial administration or, purely and simply, the intention of breaking the basis of the colonial pact. For central and southern Andes - that is the spaces corresponding to the present Republic of Peru and Bolivia - although there is still no adequate knowledge of the structure of these movements, at least there is a chronology of those. Throughout the sixteenth century, for example, movements such as the Onoya Taki (1565) or Vilcabamba (until its destruction in 1572), reflected the strength of Andes' population to its colonial subordination, at the same time they looked for the reconstruction, from the ruins, of Andean societies destroyed by the Spanish invasion. In the seventeenth century, probably as a result of a significant decline of Andean population and the relative success of colonial conditioning implemented by Toledo, was established within the dominated town a sort of pax Andean, whose expression was precisely the absence of significant Andean insurgency.